The interest students in cycling sport during the Covid-19 pandemic - Muhammad Ali; Ilham Ilham; David Iqroni (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2022)
This study aims to find out whether there is interest in SMA Negeri 5 Jambi students in cycling sport during the Covid-19 pandemic. This study is quantitative and descriptive. The instruments in this study are in the form of documentation sheets and questionnaires containing 25 questions. This study is conducted using a google form distributed to students of SMA Negeri 5 Jambi through social media. The samples of this study are 25 male students of SMA Negeri 5 Jambi who met the criteria. The test instrument used is the validity test and the reliability test. The analysis technique used in this study is descriptive, while the calculation in the questionnaire uses the percentage descriptive. The results of this study indicate that students' interest in cycling sport during the covid-19 pandemic at SMA Negeri 5 Jambi is included in the category of very good with a percentage of 88.64%, where the score was in the interval range between 85-100%.